Charge transfer states and carrier generation in 1D organolead iodide semiconductors. Issue 26 (25th June 2021) - Amerling, Eric; Zhai, Yaxin; Larson, Bryon W.; Yao, Yi; Fluegel, Brian; Owczarczyk, Zbyslaw; Lu, Haipeng; Whittaker-Brooks, Luisa; Blum, Volker; Blackburn, Jeffrey L.
Abstract : Naphthalene diimide based diammonium cations can be utilized to produce 1D organic/inorganic metal halide semiconductors with internal charge separation via charge transfer states that lie energetically below the metal-halide excitonic absorption. Abstract : Excited-state interactions between organic and inorganic components in hybrid metal halide semiconductors open up the possibility of moving charge and energy in deliberate ways, including energy funneling, triplet energy harvesting, or long-lived charge separation. In this work, we utilize π-conjugated naphthalene diimide electron accepting molecules to fabricate a hybrid one-dimensional (1D) lead iodide semiconductor ((NDIC2)Pb2 I6 ) with an internal charge separating junction. Despite recent efforts on the synthesis of 1D metal halide semiconductors, little is known about their electronic structure, optical properties, and excited-state dynamics. Steady-state and time-resolved spectroscopy measurements of ((NDIC2)Pb2 I6 ) thin films elucidate discrete optical features from the lead iodide and naphthalene diimide components of this heterostructure, along with a weakly bound optically active charge transfer state. The type-II heterojunction between the organic NDIC2 and inorganic Pb2 I6 moieties facilitates rapid separation of photogenerated charges, where charge recombination is hindered by the spatial separation of charges across the organic/inorganic interface. Our study also provides some important insights into the ways in which Coulomb interactions between the organic and metal halide moieties and π–π interactions between the organic cations can affect the crystallization of these hybrid semiconductors with large, optically active π-conjugated chromophores. We believe our findings will further enable the rational design of low-dimensional organic–inorganic heterostructures where the dielectric environment, charge transfer states, and exciton behavior may be modulated.